Breadth of external knowledge sourcing and product innovation: The moderating role of strategic human resource practices. Issue 2 (April 2017) - Ardito, Lorenzo; Messeni Petruzzelli, Antonio
Abstract: Prior research has argued that external knowledge sourcing can be supported by effective strategic human resource (HR) practices. However, whether and how the adoption of new organizational mechanisms in group settings influences the relationship between external search strategies and innovation performance represents an unanswered question. Therefore, the present paper aims to explore the relationship between the breadth of external knowledge sourcing (i.e., external search breadth) and product innovation by unveiling the moderating effects of strategic HR practices, as represented by the implementation of heterogeneous work groups and brainstorming sessions. On the basis of data from the Italian Innovation Survey, our results reveal that external search breadth is curvilinearly (inverted U) related to product innovation, and its negative effects occur later in the presence of heterogeneous work groups and brainstorming sessions.